The impact of chronic rhinosinusitis on COVID-19 risk and outcomes: A systematic review and meta-analysis - Reda, Abdullah; Lashin, Basant Ismail; Alaaraj, Mustafa Mohammad; Abouelkheir, Moustafa; Ahmed, Mahmoud Ibrahim; Shah, Jaffer; El-Qushayri, Amr Ehab (Frontiers in Immunology, 2023)
Background: The impact of chronic rhinosinusitis (CRS) and subsequent steroid therapy on acquiring COVID-19 and severe outcomes remains controversial. Therefore, we conducted this systematic review and meta-analysis to provide cumulative evidence regarding the risk of COVID-19 and the impact of steroid therapy, length of hospital stay, mechanical ventilation, and mortality among CRC patients. Methods: We conducted a comprehensive electronic search strategy using the relevant keywords. The outcomes and risk factors of COVID-19 in CRS patients was estimated and compared to a healthy control group when applicable. Results: A total of seven studies were included, with an estimated prevalence of 6.5% (95% confidence interval (CI): 2.5-15.7) for COVID-19 in the CRS group. COVID-19 prevalence did not differ between CRS and controls (odds ratio (OR): 0.92; 95%CI: 0.84-1.01; p = 0.08). Moreover, using steroid/immunosuppressive therapy did not significantly increase the risk of acquiring COVID-19 in CRS patients compared to the control group (OR: 3.31; 95%CI: 0.72-15.26; p = 0.12). Length of hospital stay, mechanical ventilation, and mortality rates were comparable between the two groups. Furthermore, we found that male sex, cardiovascular morbidity, renal diseases, and hypertension were inversely associated with COVID-19 infection (p < 0.01). Conclusion: CRS had a neutral effect on acquiring COVID-19 and developing severe outcomes. However, further studies are needed.